An Eye on Vision: 20 Questions About Vision Screening and Eye Health. (March 2018) - Nottingham Chaplin, P. Kay; Baldonado, Kira; Bradford, Geoffrey E.; Cotter, Susan; Moore, Bruce
Current evidence-based and best practice vision screening and eye health approaches, tools, and procedures are the result of revised national guidelines in the past 3 years and advances in research during the last 16 years. To help the busy school nurse with little time to keep up with changes in children's vision practices and a growing body of literature, the National Center for Children's Vision and Eye Health at Prevent Blindness is providing answers to 20 questions received most often from the field. Question topics are: (1) arranging the screening environment, (2) occluders to cover the eyes during vision screening, (3) optotype-based screening at distance, (4) optotype-based screening at near, (5) instrument-based screening, (6) muscle imbalance screening, (7) referrals, and (8) vision screening certification.